2014
DOI: 10.1007/s12013-014-0329-2
|View full text |Cite
|
Sign up to set email alerts
|

The Surfactant-Induced Conformational and Activity Alterations in Rhizopus niveus Lipase

Abstract: In this study, we have reported the effect of nonionic, anionic, cationic, and zwitterionic detergents on the enzymatic activity and structural stability of Rhizopus niveus lipase. Secondary structural changes were monitored by Far-UV CD which shows that surfactant induces helicity in the Rhizopus niveus lipase protein which was maximum in case of CTAB followed by SDS, CHAPS, and Brij-35. Similarly, tertiary structural changes were monitored by tryptophan fluorescence. We also carried out enzyme kinetics assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(27 citation statements)
references
References 25 publications
1
26
0
Order By: Relevance
“…Similar to present work activation in presence of short-chain imidazolium ionic liquids in wild-type R. oryzae lipase have been reported by Arai et al [33] during production of biodiesel fuel employing whole cell biocatalysts. This activation/inhibition profile also has been attributed to interactions between surfactant and enzyme leading to structural changes [4,32,34]. To further ascertain this different spectroscopic studies were undertaken.…”
Section: Variation In the Hydrolytic Efficiencysupporting
confidence: 88%
See 2 more Smart Citations
“…Similar to present work activation in presence of short-chain imidazolium ionic liquids in wild-type R. oryzae lipase have been reported by Arai et al [33] during production of biodiesel fuel employing whole cell biocatalysts. This activation/inhibition profile also has been attributed to interactions between surfactant and enzyme leading to structural changes [4,32,34]. To further ascertain this different spectroscopic studies were undertaken.…”
Section: Variation In the Hydrolytic Efficiencysupporting
confidence: 88%
“…In the present investigation occurrence of analogous effect could be the probable cause for observed structural changes. On the contrary Alam et al [32] reported grater increase in helical content by CTAB in R. niveus lipase with corresponding decrease in activity. The observed increase in ␤-sheet could also be attributed to loss of hydrogen bonds between water molecules and ␣-helices as seen in case of lyophilization leading to a more stable rigid structure of enzyme [45].…”
Section: Spectroscopymentioning
confidence: 86%
See 1 more Smart Citation
“…The induced changes in surface hydrophobicity of proteins upon ligand binding can be evaluated by using ANS binding since this fluorescent hydrophobic dye has a very weak fluorescence in aqueous solutions, but its fluorescence intensity increases in hydrophobic environments [24,48].…”
Section: Determination Of Protein Surface Hydrophobicity Pshmentioning
confidence: 99%
“…The positional distribution of fatty acids within TAG was analysed by limited hydrolysis of the acyl ester linkage at C-1 and C-3 with the lipase from Rhizopus niveus (62310; Sigma-Aldrich) (Alam et al, 2015;Kohno et al, 1994).…”
mentioning
confidence: 99%